Tantárgystruktúra, oktatási cél és módszer a bécsi keleti akadémia diplomataképzésében (1754–1918): STRUCTURE, PURPOSE AND METHODS OF COURSES IN TEACHING OF DIPLOMATS AT THE ORIENTAL ACADEMY IN VIENNA (1754–1918) - Bradean-Ebinger , Nelu (Közép-Európai Közlemények, 2020)
In the following paper, I’ll present the history of the well known and famous high school „Orientalische Akademie” in Vienna. The study will focus togehter with the historical issues on the teaching of the carrier diplomats in the time before the First World War retrospecting into the 19. and 18. Centuries. The paper shows as well as the conclusion that the teaching and the structure of the study projects were on a very high level. All of the needfull substances and knowledges used up for the diplomatical branch, as law, history, economics was available for the students of this school. The teaching activity in the linguistic aria was prominent in European relations too. Our study presents the methods and the very rich scale of the offering on the teaching-forms in their historical developement from 1754 into the beginning of the 20. century. Most of these methods are also used in the pedagogical praxis up to date as for example: sensomotoric style of learning, developement of the extroverted type of the individuum, grammatical interiorization in the diplomatical professional language.